Evaluation of advanced wide bandgap Semiconductor-based DC-DC converter for solar power tower tracker application - Waleed.M. Hamanah; A. Salem; Mohammad A. Abido (Alexandria Engineering Journal, 2023)
This paper studies and evaluates the advanced wide bandgap (WBG) semiconductor switches in DC drives system applied to a solar power tracker. Namely, Silicon Carbide (SiC)-based MOSFETs and Gallium Nitride (GaN)-based enhancement-mode high-electron-mobility transistors (E-HEMTs) are developed and implemented as a class E DC/DC converter while supplying a DC motor as a part of the Solar Power Tower (SPT) heliostat unit and tested under different loading conditions. Besides, a MATLAB simulation is presented to demonstrate the effectiveness of the drive system considering both indoor and outdoor to accomplish the harsh weather conditions in the Kingdom of Saudi Arabia. A SiC-based Class-E DC-DC converter has been designed, implemented, tested, and evaluated. In addition, a GAN-based DC-DC converter has been tested and evaluated in a complete DC drive system. For the sake of comparison, an identical Silicon- based class-E DC-DC converter is designed and implemented to be compared with the proposed WBG-based converters. The results demonstrate that the proposed technique for SPT drive reduces switching losses and increases the drive system efficiency without affecting the operating drive performance. It was also observed that the WBG converter is more efficient and suitable for high-temperature environments with less switching losses by 15% under an operating frequency of 20 kHz.